Re‐defininG AddiCCH3Tion: genomics and epigenomics on substance use disorders. Issue 4 (July 2014) - Rutter, Joni L.; Volkow, Nora D.
<x xml:space="preserve">Abstract</x> Genetic and epigenetic research have expanded our understanding of the neurobiological basis of substance use (SUD) and related disorders through an interdisciplinary process of human and molecular genetic research. Concomitantly, significant advances in neuroimaging have led to the recognition of the crucial role that the orchestration of gene regulation plays at specific developmental stages in human brain development. Taken together, this work has led to an increased recognition that genetic variation and gene regulation modulate vulnerability (or resilience) for SUD and that these processes are mediated though their influence on brain development, connectivity, and function, which in turn influences brain responses. <boxed-text content-type="graphic" id="mgg393-blkfxd-0001" position="anchor" orientation="portrait"> </boxed-text>